Stratégies du vertige. Trois poètes :Nicole Brossard, Madeleine Gagnon, France Théoret - Dupré, Louise (Itinéraires féministes, 1989)
Nicole Brossard, Madeleine Gagnon et France Théoret ont eu sans contredit une influence déterminante sur notre littérature. Plus qu’une étude de ces trois poètes, Stratégies du vertige nous propose de suivre un trajet amorcé dans les années 1970, au coeur des débats sur la modernité et sur l’écriture des femmes.
Keywords: amériques; arts; discipline; histoire et politique; poésie; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Beyond feminist aesthetics: Feminist literature and social change - Felski, Rita (Harvard University Press., 1989)
Beyond Feminist Aesthetics has a dual focus. First, Rita Felski gives a critical account of current American and European feminist literary theory, and second, she offers an analysis of contemporary fiction by women, drawing in particular on the genres of the autobiographical confession and the novel of self-discovery, in order to show that this literature raises questions for feminism that cannot be answered in terms of a purely gender based analysis. Felski argues that the idea of a feminist aesthetic is a nonissue that feminists have needlessly pursued; she suggests, in contrast, that it is impossible to speak of “masculine” and “feminine,” “subversive” and “reactionary” literary forms in isolation from the social conditions of their production and reception. The political value of such works of literature from the standpoint of feminism can be determined only by an investigation of their social functions and effects in relation to the interests of women in a particular historical context. This leads her to argue for an interdisciplinary approach to the analysis of literature which can integrate literary and social theory, and to develop such an approach by drawing upon the model of a feminist counter-public sphere. Rita Felski has produced a closely reasoned, stimulating book that creates a new framework for discussing the relationship between literature and feminist politics. It will interest students and teachers of women’s studies, comparative literature, cultural studies, and fiction.
Keywords: 1900-1999; changement social; cours; discipline; fem1000; occident; premier cycle; périodes historiques; thématiques; écriture des femmes*; études littéraires

Le rapt de Ganymède - Fernandez, Dominique (Bernard Grasset, 1989)
"D'après la mythologie grecque, Ganymède était le plus bel adolescent vivant sur la terre. Zeus, le dieu suprême, étant tombé amoureux du jeune homme, prit la forme d'un aigle pour l'enlever et en faire son compagnon dans le ciel. Le rapt de Ganymède est resté le symbole de l'audace nécessaire à un amour qui défie les règles communes. Quand j'étais étudiant, deux mots étaient synonymes : homosexuel et paria. Aux hommes et aux femmes de ma génération a manqué la possibilité de découvrir, chez des modèles que le monde entier admire, une légitimation de goûts que l'opinion publique réprouve sous l'épithète de "contre nature". J'ai voulu montrer, d'une part que la persécution de l'homosexualité à partir du XIXe siècle s'explique par des raisons exclusivement économiques et politiques, d'autre part que certains des plus grands esprits, des meilleurs poètes et romanciers, compositeurs de musique, peintres et cinéastes de tous les temps, de Sapho à Platon, de Whitman à Cavafy, de Melville à Yourcenar, du Caravage à David, de Mozart à Schubert, d'Eisenstein à Visconti, ont tissé un réseau d'oeuvres qui peuvent servir désormais de culture, c'est-à-dire d'exemple et d'encouragement. Bien mieux que les paternes et hypocrites absolutions prononcées depuis cent ans par les psychiatres et psychanalystes, véritable imposture de notre temps, dévoilée ici dans un sottisier réjouissant. D.F." -- Site de l'éditeur
Keywords: 1800-1899; 1900-1999; DIG; LGBTQIA2+; approches et analyses; arts; beaux-arts; cinéma; cours; discipline; europe; his4860; histoire; histoire de l'art; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; littérature homosexuelle; musique; mythologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

Toute écriture est amour - Gagnon, Madeleine; Verthuy, Maïr.; Maranda, Jeanne (Autographie, 1989)
Depuis Les Mots vivants en 1969, Madeleine Gagnon a publié plusieurs livres importants dont Lueur, Les Fleurs du Catalpa et Femmeros. Madeleine Gagnon a colligé, dans Autographie I, des textes de fiction publiés entre 1969 et 1981. Autographie II rassemble les textes de réflexion et critiques écrits parallèlement à son œuvre de fiction.
Keywords: 1900-1999; amériques; arts; canada; cours; discipline; lit3220; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Woman, native, other: Writing Postcoloniality and feminism - Minh-ha, Trinh T. (Indiana University Press, 1989)
Woman, Native, Other is located at the junction of a number of different fields and disciplines, and it genuinely succeeds in publishing the boundaries of these disciplines further ... In this first full-length study, Trinh Minh-ha examines post-colonial processes of displacement -- cultural hybridization and decentered realities, fragmented selves and multiple identities, marginal voices and languages of rupture. Working at the intersection of several fields -- women's studies, anthropology, critical cultural studies, literary criticism, and feminist theory, she juxtaposes numerous prevailing contemporary discourses in a form that questions the (male-is-norm) literary and theoretical establishment
Keywords: approches et analyses; arts; discipline; postcolonialisme; système colonial; systèmes d'oppressions; études littéraires

Malaise et révolte des femmes dans la littérature québécoise depuis 1945 - Saint-Martin, Lori; Université Laval Groupe de recherche multidisciplinaire féministe (Cahiers de recherche du GREMF, 1989)
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; amériques; arts; canada; cours; discipline; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Woman, native, other: Writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press., 1989)
"" ... Methodologically innovative ... precise and perceptive and conscious ... ""--Text and Performance Quarterly""Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color.""--Chandra Talpade Mohanty""The idea of Trinh T. Minh-ha is as powerful as her films ... formidable ... ""--Village Voice"" ... its very forms invite the reader to participate in the effort to understand how language
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; fem1000; fem3200; féminisme décolonial; littérature; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Woman, native, other: writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press, 1989)
" . . . methodologically innovative . . . precise and perceptive and conscious . . . " —Text and Performance Quarterly "Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color." —Chandra Talpade Mohanty "The idea of Trinh T. Minh-ha is as powerful as her films . . . formidable . . . " —Village Voice " . . . its very forms invite the reader to participate in the effort to understand how language structures lived possibilities." —Artpaper "Highly recommended for anyone struggling to understand voices and experiences of those 'we' label 'other'." —Religious Studies Review Audio book narrated by Betty Miller. Produced by Speechki in 2021.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires